Retrato de um Portugal migrante: a evolução da emigração, da imigração e do seu estudo nos últimos 40 anos - Pedro Góis; José Carlos Marques (e-cadernos ces)
Forty years ago, Portugal was a country of emigration that had some immigrants. Today it is a country of migrations. Between the return or repatriation of many Portuguese nationals and the reception of hundreds of thousands of foreigners, national demography gained diversity and complexity. Without immigration, we would be numerically less, and we will be poorer and older. After the announced end of emigration, we have gone through several cycles of emigration and return. Migratory outflows have never ceased to have social and sociological consequences. After all, emigration is more structural than we believed. The dynamics and diversity of the origins of migrants to Portugal, but also the multiple geography of the destinations of Portuguese emigrants represent the position change in the global migration system. Portugal is not (yet) a center, but it is (no longer) a periphery (or perhaps it still is, for some emigrants). Nationality law has evolved alongside more or less inclusive ideologies, and extended the number of citizens who are a part of the national community. Portugal is now a country in movement, full of migratory dynamics. This portrait allows us to foresee a future full of challenges regarding integration and diversity management.